2015
DOI: 10.1016/j.jbiotec.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of Xanthomonas sacchari R1, a biocontrol bacterium isolated from the rice seed

Abstract: Xanthomonas sacchari, was first identified as a pathogenic bacterium isolated from diseased sugarcane in Guadeloupe. In this study, R1 was first isolated from rice seed samples from Philippines in 2002. The antagonistic ability against several rice pathogens raises our attention. The genomic feature of this strain was described in this paper. The total genome size of X. sacchari R1 is 5,000,479 bp with 4315 coding sequences (CDS), 59 tRNAs, 2rRNAs and one plasmid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…Similar results with species like X. albilineans, X. theicola, X. hyacinthy, and X. translucens were found in previous studies forming a basal clade in the phylogeny of Xanthomonas [4,43,44]. Additionally, X. albilineans and X. sacchari presents a reduced genome comparing to the other species of the genus [24,25] comparable to Xylella fastidiosa [45].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results with species like X. albilineans, X. theicola, X. hyacinthy, and X. translucens were found in previous studies forming a basal clade in the phylogeny of Xanthomonas [4,43,44]. Additionally, X. albilineans and X. sacchari presents a reduced genome comparing to the other species of the genus [24,25] comparable to Xylella fastidiosa [45].…”
Section: Discussionsupporting
confidence: 87%
“…fragariae [24][25][26][27][28][29]. In this way, we found that the genome of the XC01 strain of X. citri pv.…”
Section: Discussionmentioning
confidence: 97%
“…These strains are isolated from surface-sterilized rice seeds. X. sontii strains are reported to be non-pathogenic towards rice, however, pathogenicity status of remaining isolates is unknown (Fang, Lin et al 2015, Bansal, Kaur et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, X. sontii, X. maliensis and some strains of X. sacchari , other Xanthomonas sp. were found to be associated with healthy rice seeds or leaves (Vauterin, Yang et al 1996, Fang, Lin et al 2015, Triplett, Verdier et al 2015, Bansal, Kaur et al 2019). Rice pathogenic Xanthomonas are widely studied, however, their non-pathogenic counterparts isolated from healthy plants are vastly overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthomonas arboricola is known to comprise pathogenic strains of different pathovars affecting stone and nut fruit trees (13); nonpathogenic X. arboricola strains are also isolated from walnut trees (11,12). Another well-studied nonpathogenic strain, Xanthomonas sacchari R1, was isolated from rice seeds and is known to be antagonistic to rice pathogens, which was later identified as a misclassified strain of X. sontii (14,15). In addition to these, there are various unclassified and unexplored nonpathogenic isolates reported from a diversity of host plants (16).…”
mentioning
confidence: 99%